Dialogue - Ford, Cameron M.; Drazin, Robert; Glynn, Mary Ann; Kazanjian, Robert (Academy of Management Review, 2000)
The article focuses on a comment on a previous article concerning multilevel models of organizational creativity and the writers' response. It states that the original article raises critical issues concerning the definition of creativity and suggests that creativity should be defined in respect to creative actions and outcomes as this has methodological and conceptual advantages that can assist in future research. It mentions that the article should not have been dismissal of previous research and instead could utilize that research by recasting the empirical research within a holistic description focusing on individual thought and action. The authors response defends their position and states that theories can have the virtue of generalizability, simplicity, and accuracy.